(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Modal verbs are an essential part of English grammar. They help speakers express ability, possibility, permission, obligation, advice, and necessity. This article examines the functions of modal verbs, their grammatical characteristics, and their importance in effective communication. The study analyzes the most commonly used modal verbs and discusses their role in developing English language proficiency.